PENGARUH ALOKASI ANGGARAN PEMERINTAH PADA SEKTOR PERTANIAN DAN SEKTOR INDUSTRI TERHADAP PDRB KOTA SUNGAI PENUH - Harum Fadhila Novrianti; Zamzami; Sri Ningsih (STKIP Subang, 2026)
This study aims to analyze the development trends of Gross Regional Domestic Product (GRDP), the development trends of budget allocations in the agricultural and industrial sectors, and the influence of budget allocations in the agricultural and industrial sectors on GRDP in Sungai Penuh City for the period 2010–2024. This study uses secondary time-series data analyzed with multiple linear regression (Ordinary Least Squares/OLS) using EViews 12. The results indicate that GRDP in Sungai Penuh City, as well as budget allocations in the agricultural and industrial sectors, tended to increase during the study period. The regression results show that the agricultural sector budget partially has a negative and significant effect on GRDP, while the industrial sector budget has a positive and significant effect on GRDP. Simultaneously, the agricultural and industrial sector budgets significantly influence GRDP in Sungai Penuh City. The coefficient of determination (R²) of 0.910335 indicates that 91.03% of the variation in GRDP can be explained by these two variables, while the remainder is explained by other factors outside the research model.